2022
DOI: 10.5796/electrochemistry.22-00018
|View full text |Cite
|
Sign up to set email alerts
|

Cycle Degradation Analysis by High Precision Coulometry for Sulfide-Based All-Solid-State Battery Cathode under Various Potentials

Abstract: All-solid-state batteries (ASSBs) using sulfide-based solid electrolytes (SEs) are promising energy storage devices beyond the present liquid-type lithium-ion batteries (LIBs) using organic solvents, which are expected to realize the adaptation of new systems such as higher-voltage cathodes. However, in recent years, undesirable side reactions are being reported in the nanometer-order region at the interface of cathode active materials/SEs. Therefore, we evaluated the cycle durability of the all-solidstate cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…The sample preparation, the ASSB cell fabrication, and the durability test have been explained in detail in a previous paper ,,, and will only be briefly described here.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample preparation, the ASSB cell fabrication, and the durability test have been explained in detail in a previous paper ,,, and will only be briefly described here.…”
Section: Methodsmentioning
confidence: 99%
“…Floating test sequence at constant potential (CP) was conducted at potentials of 4.25−4.55 V vs Li/Li + for 120 h at 60 °C. During the cycle test, physical cell degradation, such as cracking of NCM523 particles and the reduction of the contact with the SE, due to the expansion and contraction of the cathode active material, cannot be avoided at higher potential, 23 whereas the number of charge/discharge cycles in floating tests can be reduced to a minimum to focus on chemical degradation. Before the floating test, the halfcells were charged to 4.25, 4.35, 4.45, and 4.55 V vs Li/Li + at a constant current (CC) of 200 μA cm −2 (defined as C-rate of 0.1).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 In cycling testing, physical degradation such as cracking of cathode active material due to expansion and contraction is added to lead more complex degradation mode. 17 Therefore, in this study, we adopted the floating test to reduce to a minimum cycle number. Before the floating test, the half cells were charged to 4.25 and 4.55 V vs Li/Li + at a constant current (CC) of 200 μA cm −2 (defined as a Crate of 0.1) and discharged to 3.0 V vs Li/Li + at a CC of 0.1 C-rate.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…However, ASSBs employing sulfide-based SEs have some problems: vulnerability of the sulfides, expansion–contraction influence of active materials, low reduction durability for lithium metal anodes, and oxidative decomposition side reactions at the interface of the SE/cathode active material. ,,, Among these, we focused on the cathode side as it often determines ASSB performance in terms of cell resistance and capacity. The chemical/physical/mechanical issues of ASSB cathodes employing inorganic SEs are simplified by Banerjee et al We investigated the degradation mechanism of the sulfide-based argyrodite-type SE Li 6 PS 5 Cl/LiNbO 3 -coated LiNi 0.5 Co 0.2 Mn 0.3 O 2 (NCM523) employing various techniques, such as electrochemical impedance spectroscopy, time-of-flight secondary-ion mass spectrometry (ToF-SIMS), , electron energy loss spectroscopy, X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), ,, electron diffraction (ED), and X-ray absorption spectroscopy (XAS) . The results indicated that almost no degradation was observed on the NCM523 cathode active material side and that degradation near the interfacial region of the SE/LiNbO 3 coating was more dominant.…”
Section: Introductionmentioning
confidence: 99%